Membangun Kemandirian Santri: Peran Wali Asuh di Pondok Pesantren Darussa’adah Lirboyo - Zahra, Ipah; Khoiruddin, M. Arif (Journal of Islamic Education, 2023)
The aim of this research is to understand the role of foster carers in providing education and guidance that can increase the independence of students at the Darussa'adah Lirboyo Islamic boarding school in social, emotional and religious aspects. In addition, it identifies environmental factors, parents and foster carers that can influence the level of independence of students, so that necessary corrective steps can be identified. This research uses a qualitative research method with a case study approach. The data taken involved foster carers, students, and the administrator of the Darussa'adah Lirboyo Islamic boarding school as primary data sources. Data collection will be carried out through in-depth interviews, observation and documentation studies. The research results show that the role of foster carers in educating and fostering the independence of students at the Darussa'adah Lirboyo Islamic boarding school is very significant. Foster guardians have an important role in accompanying and guiding every aspect of the students' daily lives, including religious practices, study activities and extracurricular activities. They act as substitute parental figures in Islamic boarding schools and provide good examples through positive behavior and advice. In education and fostering independence, foster carers train students to be independent in terms of personal hygiene, time management and responsibility. They also provide encouragement, motivation and enthusiasm to students in facing various challenges, thereby increasing students' self-confidence and enthusiasm for learning.